The Role of Cbdcs in Promoting International Financial and Trade Transactions - Fahad, Aysar Y.; Abdurrazaq, Taib Othman (American Journal of Economics and Business Management, 2023)
The article deals with financial planning and control in the system of financial management of the corporate sector of the economy. Advantages of budget planning, stages of the budget process. Methods of budgeting in large organizations, the classification of general and specific principles has been carried out. The grouping of operating and financial budgets of the corporation is given. The necessity of financial control at the final stage of budgeting is proved.